On the northernmost record of Pritha (Aranei: Filistatidae) in the Caucasus and entire Asia with notes on Filistatidae from Caucasus - Marusik YM; Seropian A; Koponen S (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2022)
Pritha pallida Kulczynski, 1897, a species previously known from Madeira to Western Greece, has been found in Georgia. This species is illustrated, and its distribution is commented and mapped. The distribution and taxonomic status of all Filistatidae species known from the Caucasus are briefly discussed.